Produzindo práticas e saberes na atenção psicológica grupal a idosos residentes em asilos na cidade de Assis-SP - Maia, Gabriela Maria Ramos [UNESP]; Gonçalves, Aline Mendes [UNESP]; Garcia, Juliana Silva [UNESP]; Cunha, Lilian da Silva [UNESP]; Cagnin, Wlademir Luther Falcão [UNESP]; Almeida, Flávia Mendes Ferraz de [UNESP]; Correa, Mariele Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Through the extension Project “Producing practices and knowledge in group care to nursing home residents in the city of Assis-SP” we seek, through a cooperative work with the “Lar dos Velhos” (Home of the Elder) asylum, to problematize and break with the biopolitics and the condition of subjection present at the ILPIs (Long Permanence Institutions for Elders), providing psychosocial care practices that value the singularities, the knowledge, the experience and the desires of the institutionalized elderly. In that way, we aim to promote greater interventions of the Psychology in the aging processes and deconstruct stereotyped social visions of fragility and incapacity associated with old age, emphasizing the possibilities and rights of this population as a way to increase the potency of their existence.

Por meio do projeto de extensão “Produzindo práticas e saberes na atenção grupal a idosos residentes em asilos na cidade de Assis-SP”, buscamos, através de um trabalho em rede com o asilo “Lar dos Velhos”, problematizando e buscando romper com a lógica biopolítica e a condição de assujeitamento presentes nas ILPIs, proporcionando práticas de atenção psicossocial que valorize as singularidades, os saberes, as vivências e os desejos dos(as) idosos(as) asilados(as). Nesse sentido, almejamos promover maiores intervenções da Psicologia nos processos de envelhecimento e descontruir visões sociais estereotipadas de fragilidade e incapacidade da velhice, enfatizando as possibilidades e os direitos pertencentes a essa população como forma de potencializar sua existência.
Keywords: Asylum; Aging; Subjectivity; Asilos; Envelhecimento; Subjetividade